Stochastic Channel Modeling for Railway Tunnel Scenarios at 25 GHz. Issue 1 (15th February 2018) - He, Danping; Ai, Bo; Guan, Ke; Zhong, Zhangdui; Hui, Bing; Kim, Junhyeong; Chung, Heesang; Kim, Ilgyu
Abstract : More people prefer using rail traffic for travel or for commuting owing to its convenience and flexibility. The railway scenario has become an important communication scenario in the fifth generation era. The communication system should be designed to support high‐data‐rate demands with seamless connectivity at a high mobility. In this paper, the channel characteristics are studied and modeled for the railway tunnel scenario with straight and curved route shapes. On the basis of measurements using the "Mobile Hotspot Network" system, a three‐dimensional ray tracer (RT) is calibrated and validated for the target scenarios. More channel characteristics are explored via RT simulations at 25.25 GHz with a 500‐MHz bandwidth. The key channel parameters are extracted, provided, and incorporated into a 3rd‐Generation‐Partnership‐Project‐like stochastic channel generator. The necessary channel information can be practically realized, which can support the link‐level and system‐level design of the communication system in similar scenarios.